Analysis of Perfluoroalkyl Carboxylic Acids in Composite Dietary Samples by Gas Chromatography/Mass Spectrometry with Electron Capture Negative Ionization - Fujii, Yukiko; Harada, Kouji H; Koizumi, Akio (Environmental science & technology, 2012)
A gas chromatography–mass spectrometry and electron-capture negative ionization (ECNI) method was developed to quantify perfluorinated carboxylic acids (PFCAs) in composite dietary samples. Benzyl esterification was used for pretreatment before PFCAs analysis. This stabilized the benzyl radical leaving group preferentially, and gave carboxylic anions of the PFCAs with ECNI. The method had a low detection limit (0.3–10 pg g–1) and good recoveries (98–90%) for PFCAs with 8–14 carbon atoms (C8 to C14). The method was applied to 24-h dietary samples from subjects in Japan (Hokkaido, Kyoto, and Okinawa; 1992 to 2007, and 2009), Korea (Seoul; 1994 and 2007), and China (Beijing; 1993 and 2009). The levels of the PFCAs were between 39 and 169 ng day–1 in Korea, 58 and 71 ng day–1 in China, and 56 and 67 ng day–1 in Japan. Between the two sampling years, the total levels of PFCAs (C8 to C14) increased significantly (p < 0.05). The interaction between the sampling location in Korea and year was significant (p < 0.05).